RANCANG BANGUN WEBSITE PROFIL UMKM PISTACIO MENGGUNAKAN MODEL WATERFALL UNTUK MENINGKATKAN PEMASARAN DIGITAL - Maulida Azzahra; Ahmad Rafli Oktavianto; Imam Hanafi; Hidayatullah Al Islami (Journal of Research and Publication Innovation, 2025)
In the current digital era, the use of information technology has become a vital component in increasing business competitiveness, including for micro, small, and medium enterprises (UMKM) in Indonesia. UMKM Pistacio is a local culinary business that faces challenges in promotion and delivering comprehensive business information. To address these issues, a company profile website was designed and developed using the Waterfall method. This website aims to help UMKM Pistacio establish a professional digital identity, broaden its promotional reach, and simplify information management. The system development process involved requirement analysis, system design, implementation, testing, and maintenance. The design includes user interface and experience (UI/UX) prototypes created with Figma, UML diagrams (activity diagram, use case diagram, ERD), flowcharts, and a structured database. The website features two main interfaces: a customer-facing side displaying menu, business information, and external ordering links, and an admin side for managing website content independently. The implementation showed that the system effectively meets the business needs by presenting information in an appealing and structured way. Moreover, the website serves as an alternative to third-party platforms like GoFood, GrabFood and ShopeeFood. Through this website, UMKM Pistacio is expected to improve its digital presence and competitiveness in the online market.